Telemedicine Development for Health Center Services Using Agile Methods - Lahru Riatma, Darmawan; Masbahah; Anis Laela Megasari; Rizka Adela Fatsena (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
Puskesmas are the spearhead of health services throughout Indonesia, puskesmas are at the forefront in breaking the chain of transmission of COVID-19 because they are located in every sub-district and have a regional concept. Being at the forefront in handling COVID19 and continuing to provide other primary health services to the community is a tough task for puskesmas throughout Indonesia. In urgent situations and rapidly changing regulations regarding the handling of COVID19 and non-COVID19 patients, telemedicine application development researchers are required to work quickly and precisely according to the needs of the Puskesmas. This study discusses the development of telemedicine applications using the Agile development method, with the Scrum framework. Based on the problems above, researchers will develop telemedicine applications with several health service features, namely; COVID19 independent health checks, village doctor and midwife consultations, medicine orders, maternity services, and dental consultation services, the features in the telemedicine application were developed using the agile scrum method. Telemedicine development begins with system design analysis, UI/UX design, develop, functional testing, usability testing and launching. From the system design analysis, it produces output use case diagrams and class diagrams, according to the needs of the puskesmas business process. UI/UX design is carried out using figma tools, then application development is carried out focusing on the frontend and backend, after the application has been developed, functional testing is carried out three times and usability testing. The results of the usability test conducted on 35 respondents obtained an average score through the SUS questionnaire with a score of 79. In terms of the Acceptability Range, this application program is in the Acceptable category, while on the Grade Scale it is in Grade C position and on the Adjective Rating it is in a Good position . The results show that the telemedicine application for Pusline is good and can be accepted by users.